Existing Status and Practices of Fish Farming in Trishal Upazila of Mymensingh District - Sheheli, S; Fatema, K; Haque, SM (Progressive Agriculture, 2014)
The study was conducted to investigate the existing status and practices of fish farming. A total of 100 farmers were interviewed by using a structured interview schedule from three villages (Porabari, Mathabari and Vabanipur) of Trishal upazila of Mymensingh district at their houses and/or farm sites during January to May 2013. Most of the farmers (89%) made profit from fish production. The study confirmed that most farmers have improved their socio-economic conditions through fish production which plays an important role in increasing income, food production and employment opportunities. Five major areas are identified to improve the existing fish farming situation, which are quality fry, credit facilities, low-cost quality feed, training, and marketing channel. The impact analysis of fish farming on livelihood of fish farmers shows that overall 64% fish farmers have increased overall livelihood from fish farming during the last four years (2010-2013). Access to micro-credit, provide good quality input such as fry, feed, vaccines, etc., market facilities, supply of improve technologies, and provide training all lead to increased fish production. The constraints index (CI) analysis shows that overall 74% fish farmers faced medium constraints for fish farming. A total of nine (9) main constraints identified hindering their fish farming, and major constraints are high production cost, lack of technical knowledge and inadequate supply of good quality fry etc. DOI: http://dx.doi.org/10.3329/pa.v24i1-2.19172 Progress. Agric. 24(1&2): 191 - 201, 2013